Nasution - Aidilla, Amelia; Nasution, Belli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Local government has started to give special attention in Riau Tourism sector lately. Riau tourism potential has been promoted. One of them is Rupat Island. Rupat Island has an interesting ocean tourism in Riau. Online news become a tool in spreading information among many medias. According to Undang-Undang No. 40 Tahun 1999 about Pers explaining that online media is a product of mass media if it is based on pers’ ethical code. Writer used qualitative descriptive methode. Writer used framing analysis Pan and Kosicki and agenda setting theory. Object of the research is news related to Pulau Rupat tourism in tripriau.com’s Wisata rubric from 19 April until 20 June 2016. Result shows that there is a framing from news’ syntax and rethoric. Meanwhile, for media agenda, tripriau.com focus on presenting Rupat as a tourism destination. With a feature packaging, tripriau.com only presents news that media wants. The negative things that Rupat has almost dissapear from the news. Point of view in this news comes from journalist’ and interviewer’ side. Though, tripriau.com keep maintaining its media idelogy in delivering news. Keywords : Famming Analysist, Agenda Setting Theory, and Ideology of Media